KONSELING ADIKSI NARKOBA DENGAN MENERAPKAN KOMUNIKASI INTERPERSONAL - Anak Agung Gede Agung Putra Dalem; Ni Luh Sri Mahendra Dewi (Widyasrama, 2022)
According to BNN (Badan Narkotika Nasional) data, Bali has 1,8 prevalencies of drugs victims, it mean that there are over then fivty thousand of drugs victims in Bali. To handle this problem, rehabilitation programme is really needed. In all those rehabilitation programme there is call a addiction counseling. Addiction counseling is a process to giving advice or information to handling problem using drugs that can couse illness and addicted. Indicator of interpersonal communication that was implemented in addiction counseling are listening, focus on messege, eye contact, touch, self-disclosure, and motivation.